Pendampingan Optimalisasi Digital pada Social Enterprise di Batam - Jannah, Izzatul; Imanez Desta Anria; Riskiyani Putri Nandika; Dzakya Husnul Haura; Julia Ariani Utami; Catrin Virginia Saragi; Astica Wulan Dani; Zaskia Nazwa Maharani; Adika Triyansyah; Muhammad Raghib Alghifari; Susi Lestari; Nadia Fathurrahmi Lawita; Dewi Junita; Sarah Ulfah Al Amany; Mega Mayasari; Arif Darmawan; Danar Irianto; Muhammad Ikhlash (Jurnal Pengabdian kepada Masyarakat Politeknik Negeri Batam, 2025)
This community service activity aims to enhance the capacity of social enterprise actors in Batam City through training and mentoring on the use of digital applications. Social enterprise is a form of enterprise that is not only profit-oriented but also has a social mission to create a positive impact on the community. Prior to the training, the implementation team conducted interviews and data collection to identify the level of digital literacy, technology needs, and challenges faced by the social enterprise actors. The data collection results showed that most social enterprise actors have high motivation to develop but are still limited in their mastery of digital technology and online marketing. The digital application training activities, carried out by lecturers and students of the Batam State Polytechnic, were then focused on the use of Microsoft Excel and Canva digital applications. These two applications were chosen based on the priority needs of the Social Enterprises, which are expected to assist in financial management, promotion, and increasing the operational efficiency of their social businesses. Through this training, social enterprise actors are expected to be able to optimize digital technology to expand the social and economic impact of their businesses. This activity is a strategic step in driving digital transformation based on community empowerment.